Composite CuFe1-xSnxO2/p-type silicon photodiodes - Al-Sehemi, Abdullah G.; Mensah-Darkwa, K.; Al-Ghamdi, Ahmed A.; Soylu, M.; Gupta, R. K.; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2017)
CuFe1-xSnxO2 composite thin film/p-type silicon diodes were prepared on substrate by sol-gel method (x = 0.00, 0.01, 0.03, 0.05, 0.07). The structure of CuFe1-xSnxO2 composite thin films was studied using XRD analysis and films exhibited amorphous behavior. The elemental compositions and surface morphology of the films were characterized using SEM and EDX. EDX results confirmed the presence of the compositional elements. The optical band gap of CuFe1-xSnxO2 composite thin films was determined using the optic spectra. The optical band gaps of the CuFe1-xSnxO2 composite thin films were calculated using optical data and were found to be 3.75, 3.78, 3.80, 3.85 and 3.83 eV for x = 0.00, 0.01, 0.03, 0.05 and 0.07, respectively. The photoresponse and electrical properties of the Al/CuFe1-xSnxO2/p-Si/Al diode were studied. The barrier height and ideality factor were determined to be averagely 0.67 eV and 2.6, respectively. The electrical and photoresponse characteristics of the diodes have been investigated under dark and solar light illuminations, respectively. The interface states were used to explain the results obtained in present study. CuFe1-xSnxO2 photodiodes exhibited a high photoresponsivity to be used in optoelectronic applications. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Composites; Heterojunction; Light-sensing